Analisis Penerapan Model Discovery Learning dalam Microteaching Bahasa Jerman Tema Einkaufen - Azza Akira Syakirina; Nomi Merland Lumbantoruan (CV Edu Tech Jaya, 2026)
German language learning in microteaching activities tended to remain teacher-centered, resulting in limited student engagement, particularly in the Einkaufen topic which required communicative competence. This study aimed to describe the implementation of the discovery learning model and to analyze its effect on students’ engagement and understanding. The study employed a descriptive qualitative approach involving students of the German Language Education Study Program who participated in microteaching classes. Data were collected through observation and documentation of lesson plans, and were analyzed using data reduction, data display, and conclusion drawing, supported by source triangulation. The results showed that the implementation of discovery learning had been carried out through six stages: stimulation, problem statement, data collection, data processing, verification, and generalization. The model increased student engagement, as reflected in active participation in discussions, questioning, and role-play activities. In addition, students’ understanding of vocabulary and communicative expressions in shopping contexts was relatively good. However, the implementation of the verification and generalization stages had not been optimal. Therefore, discovery learning was considered effective in improving engagement and understanding, although improvements were needed in the final stages to achieve more optimal learning outcomes.